We need it: How Digital Marketing Tactics Influence the Purchasing Behaviour of Nigerian Millenials - Oyenuga Michael Oyedele; Akhaine Mary Enose; Omale Sunday Alewo (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2023)
Businesses have come to the realization that customers of today especially the millenials are actively engaged over the internet and to give them place utility, they need to engage them digitally. The objective of this study was to determine the influence of selected digital marketing tactics and their influence on the purchasing behavior of Nigerian Millenials. Research was conducted using cross-sectional survey design with data collected using close ended questionnaires designed with 5-point Likert scale questions. The study’s population comprised active internet subscribers in FCT within the millennial age group, and a sample size of 400 was arrived at using Taro Yamani’s formula. Linear regression analysis was used to test all three hypotheses, and results showed that all two selected digital marketing tactics (social media marketing and search engine optimization) have positive influence on purchasing behavior of Nigerian Millenials. Thus, it was concluded that increased use of digital marketing tactics would positively affect the purchasing behavior of Nigerian Millenials.